2007
DOI: 10.1128/aem.01415-06
|View full text |Cite|
|
Sign up to set email alerts
|

Respiration and Growth of Shewanella decolorationis S12 with an Azo Compound as the Sole Electron Acceptor

Abstract: The ability of Shewanella decolorationis S12 to obtain energy for growth by coupling the oxidation of various electron donors to dissimilatory azoreduction was investigated. This microorganism can reduce a variety of azo dyes by use of formate, lactate, pyruvate, or H 2 as the electron donor. Furthermore, strain S12 grew to a maximal density of 3.0 ؋ 10 7 cells per ml after compete reduction of 2.0 mM amaranth in a defined medium. This was accompanied by a stoichiometric consumption of 4.0 mM formate over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 46 publications
0
43
1
Order By: Relevance
“…Shewanella decolorationis S12, previously isolated from activated sludge of a textile-printing wastewater treatment plant in Guangzhou, China (Xu et al 2005), can also effectively reduce azo dyes with many organic substances and hydrogen as electron donors (Hong et al 2007a). The dissimilatory azoreduction of S. decolorationis S12 is a process linked to bacterial electron transport chain and has been proved to be a new form of microbial anaerobic respiration (azorespiration) (Hong et al 2007c(Hong et al , 2009). Further studies have found that the breakdown products of azo dyes can be completely mineralized under microaerophilic or aerobic conditions by S. decolorationis S12 (Hong et al 2007b;Xu et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Shewanella decolorationis S12, previously isolated from activated sludge of a textile-printing wastewater treatment plant in Guangzhou, China (Xu et al 2005), can also effectively reduce azo dyes with many organic substances and hydrogen as electron donors (Hong et al 2007a). The dissimilatory azoreduction of S. decolorationis S12 is a process linked to bacterial electron transport chain and has been proved to be a new form of microbial anaerobic respiration (azorespiration) (Hong et al 2007c(Hong et al , 2009). Further studies have found that the breakdown products of azo dyes can be completely mineralized under microaerophilic or aerobic conditions by S. decolorationis S12 (Hong et al 2007b;Xu et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…The disappearance of amaranth (azo reduction) was accompanied by stoichiometrical consumption of formate over time of incubation. Based on the calculation, formate consumption and amaranth reduction were in good agreement for the following reaction: Ar1– N  =  N –Ar 2  + 2COOH– + 2H 2 O → Ar1–NH 2  + H 2 N–Ar 2  + 2HCO 3 −  + 2H + (Hong et al 2007a). In addition, both Shewalella sp.…”
Section: Azo Reduction Coupled To Oxidation Of Electron Donorsmentioning
confidence: 79%
“…In addition to electricity generation, riboflavin-stimulated EET were also founded in Fe(III) and amaranth (an cell membrane-impermeable azo dye; Hong et al, 2007) reduction of MT-S12 biofilms (Supplementary Figure S4). These results suggested that although OMCs were eliminated, the electron transfer from MT-S12 to electrode could also be stimulated by higher concentration of electron mediators.…”
Section: Resultsmentioning
confidence: 99%